Human rights protection during armed conflicts: problem aspects - Никифорак, Володимир Михайлович (Primmate, Colombia, 2024)
The purpose of the article is a comprehensive analysis of problematic aspects of legal responsibility for human rights violations during armed conflicts. To achieve the goal, the following methods were used: systematic, logical and semantic, formal legal, comparative legal, formal logical, formal dogmatic, analysis. The article argues the approach according to which armed conflicts are characterized by a total violation of rights, among which the following fundamental rights are the most violated: the right to life, the right not to be subjected to torture, inhuman treatment, enforced disappearance and the right to a trial. It was concluded that these rights are the "immutable core of human rights" that cannot be violated, the characteristic features of which are: fundamentality, inalienability, inalienability and objective necessity. The development of additional regulatory and institutional guarantees for the protection of these rights and effective ways to bring perpetrators to criminal and international responsibility requires coordinated work of various institutions. Combating and counteracting human rights violations in time of armed conflict requires the united efforts of nations to eradicate aggressive warfare and the use of weapons.
ЗАХИСТ ПРАВ ЛЮДИНИ ПІД ЧАС ЗБРОЙНИХ КОНФЛІКТІВ: ПРОБЛЕМНІ АСПЕКТИ
Keywords: human rights, armed conflict, immutable core of rights, protection of human rights, legal responsibility for human rights violations